Dance of the nomad : a study of the selected notebooks of A.D. Hope - McCulloch, A. M. (Ann M.), 1949- (Pandanus Books, 2005)
The notebooks of A.D. Hope are a portrait of the contradictory essence of one of Australia's finest poet's intellect and character. Seeking to find pathways through the maze of an intellectual life, this is a profound and timely contribution to Australia's literary scholarship. Revealing the originality of his thinking and the astonishing range of his reading and interests, this edition is a testament to the intellect of one of Australia's towering literary figures.